APLIKASI FORMULASI RANSUM DENGAN MENGGUNAKAN HIJAUAN LEGUMINOSA SEBAGAI PAKAN DASAR PENYUSUNAN RANSUM SAPI DI DESA JUNGUTAN KABUPATEN KARANGASEM - Trisnadewi A. A. A. S; I G. L. O. Cakra; I M. Mudita; I W. Wirawan; E. Puspani; I K. M. Budiasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2013)
The community service was conducted in Jungutan Village, Karangasem Regency and was aimed to improvethe farmers knowlegde especially the members of farmers groups about the utilization of leguminose forage asbasal ration for ruminant. The services was conducted on Sunday, 2nd September 2012 at Wana Sari Groups ofFarmers at Banjar Untalan, Jungutan Village, and attended by 20 from 24 total members of farmers’ groups(83.33%). The methods used were direct instruction and discussion to the farmers. Almost 43% members offarmers’ groups have been given leguminose besides grass and 57% only given grass as Bali cattle feed. The resultof the services showed that the farmer’s awareness and knowlegde improved to give leguminose forage such asGliricidia sepium, Caliandra callothyrsus, and Leucaena leucochepala, besides grass feeding as basal ration forBali cattle. The utilization of forage need to be applied because of high energy and protein content in leguminoseforage, therefore the dry matter consumption will improve. The nutrient requirement could fulfill and will impactto the improvement of Bali cattle growth and production.